STRENGTH IN DIFFERENCES: EXPLORING PLURALISM'S IMPACT ON DEMOCRACY - Peer Amir Ahmad (RADJA PUBLIKA, 2023)
The study explores pluralism in democratic contexts, aiming to elucidate its significance and impact on the functioning of democratic systems. It employs qualitative content analysis and quantitative surveys across diverse democratic societies. Through a systematic review of academic literature and policy documents, the research provides a theoretical foundation for understanding pluralism's historical evolution and theoretical underpinnings. Quantitative surveys capture empirical data, allowing for the assessment of pluralism's practical implications, including its role in promoting inclusivity, representation, and political stability. Case studies provide clear insights into context-specific dynamics. The study concludes by offering recommendations to enhance the role of pluralism in strengthening democracy, fostering inclusivity, and contributing to the resilience and adaptability of democratic systems in an increasingly diverse world. Ultimately, it underscores the essential nature of pluralism as a driving force behind democratic strength and vitality.